Are the Portuguese ready for the future of tourism? A technology acceptance model application for the use of robots in tourism - Martins, Mariana Santos (2021)
The tourism sector has been growing exponentially in Portugal over the last few years, becoming increasingly competitive. On the other hand, the use of machines, robots and artificial intelligence in this industry that is built by and for people, has also been increasing and diversifying. The objective of this investigation focuses on the study of variables that can affect the acceptance of robots by the Portuguese public. The Technology Acceptance Model (TAM) is applied to understand the influence of a set of sociodemographic variables, travel behavior, motivation, and attitude towards technology in general in the perceived ease of use and perceived usefulness of using robots in tourism. The results obtained demonstrate that the Portuguese case is similar to that of other Western countries, with gender, age, travel group, motivation and attitude towards technology having a significant impact on the dependent variables.